2013
DOI: 10.1016/j.ophtha.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ABCA4 Disease-Associated Alleles in Autosomal Recessive Retinal Dystrophies

Abstract: Objective To provide a comprehensive overview of all detected mutations in the ABCA4 gene in Spanish families with autosomal recessive retinal disorders, including Stargardt disease (arSTGD), cone-rod dystrophy (arCRD), and retinitis pigmentosa (arRP). Also, to assess genotype-phenotype correlation and disease progression in 10 years by considering type of variants and age of onset. Design Case series. Participants A total of 420 unrelated Spanish families: 259 arSTGD, 86 arCRD and 75 arRP. Methods Spani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 21 publications
8
65
1
5
Order By: Relevance
“…Mutations in known genes are estimated to contribute to IRD pathology in about 50% of dominant cases (Daiger, 2004). Whereas, in recessive conditions, mutations in known genes contribute to 40-50% of cases (Riveiro-Alvarez et al, 2013). The rate of detection of causative mutations in our study conducted between 2009 and 2011 is consistent with earlier reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…Mutations in known genes are estimated to contribute to IRD pathology in about 50% of dominant cases (Daiger, 2004). Whereas, in recessive conditions, mutations in known genes contribute to 40-50% of cases (Riveiro-Alvarez et al, 2013). The rate of detection of causative mutations in our study conducted between 2009 and 2011 is consistent with earlier reported findings.…”
Section: Discussionsupporting
confidence: 92%
“…At present, a clear correlation between ABCA4 genotype and retinal phenotypes has not been well established, [42][43][44][45][46] and only one model based on a paper from Maugeri et al 47 has been proposed. Some authors report higher frequency of severe retinal phenotypes in patients carrying null ABCA4 variants, 48,49 and some specific genotypes have been associated with peculiar clinical features. 50 Despite substantial progress in determining the causal genetic variations, some ambiguities are still present because in clinically confirmed ABCA4 disease no mutations are found, suggesting that a significant revision of diagnostic screening and assessment of ABCA4 variations is needed in retinal diseases etiology.…”
Section: Resultsmentioning
confidence: 99%
“…For those cases that skipped our screening strategy, a second analysis based on a more specific strategy can be considered, such as disease-specific arrays (Asper custom-designed arrays), NGS-based methods or multiplex ligation-dependent probe amplification for some of the genes with a high prevalence of cases reported with genomic rearrangements [17,18,19,20,34,35,36,37,38,39,40,41,42,43]. Thus, our strategy or the combined use of our approach with a more specific (and expensive) one could result in a useful fast and cost-effective strategy for diagnostic purposes in cases of IRD.…”
Section: Discussionmentioning
confidence: 99%